Pengaruh Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Karyawan PT G4S Security Service Jakarta Selatan - Amanda Elvia Fauziah; Nurdinni Tilova (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to examine the influence of leadership and work discipline on employee performance at PT  G4S Security Service, South Jakarta. The research employed a quantitative analysis method, utilizing numerical data from a total of 67 respondents, who are employees of PT  G4S Security Service, South Jakarta. The sampling method used in this study was sampling technique with the Slovin formula to determine the sample size. Data processing and analysis techniques included instrument testing, classical assumption testing, descriptive analysis, quantitative analysis, and hypothesis testing.The results show that the influence of leadership on employee performance is represented by the regression equation Y = 25.557 + 0.598 X1. Hypothesis testing indicates that the calculated tvalue is greater than the ttable value (5.440 > 1.668). Therefore, H0 is rejected and H1 is accepted, indicating a positive and significant partial effect of leadership on employee performance. Similarly, the influence of work discipline on employee performance is represented by the regression equation Y = 21.399 + 0.838 X2. Hypothesis testing results show that the calculated tvalue is greater than the ttable value (6.459 > 1.668). Thus, H0 is rejected and H2 is accepted, indicating a positive and significant partial effect of work discipline on employee performance.Furthermore, the influence of leadership and work discipline on employee performance simultaneously is represented by the regression equation Y = 12.319 + 0.380 X1 + 0.632 X2. The results of hypothesis testing show that the calculated Fvalue is greater than the Ftable value (31.241 > 2.17). Therefore, H0 is rejected and H3 is accepted, meaning that leadership and work discipline have a positive and significant simultaneous effect on employee performance at PT G4S Security Service, South Jakarta.